PREDICTION MODELS FOR OLFACTORY METABOLIC AND SOWS %RNAreticulocyt (RNArt) BY MEASUREMENT OF ATMOSPHERIC AMMONIA EXPOSURE AND MICROCLIMATE LEVEL - Mushawwir, A.; Adriani, L.; Kamil, K.A. (Diponegoro University, 2011)
Twenty sows housed indoors in individual stalls were used to determine the relationships betweenatmospheric ammonia exposure and microclimate on olfactory metabolic and sows RNAreticulocyt, and toknow the prediction models of the olfactory metabolic and sows RNAreticulocyt by measurement ofatmospheric ammonia exposure and microclimate level. Result indicated a significantly negative effectof ammonia on commonly olfactory metabolic parameters and %RNAreticulocyt. The results also showedthat ammonia has been reduced the function of olfactory receptors and activities of Ca2+-gated chloridechannel open and efflux of Cl- to depolarize cell, as soon as reducing an electrical signal to the brain, sogives impact to blood metabolism (especially RNAreticulocyt). Simultaneous effect between ammonia andhumidity proved to be a good indicator for predicting model of olfactory metabolic, and %RNAreticulocytespecially for creatine kinase (=16.65+0.02H-0.59A), glucose (=21.55-0.10H-0.01A), lactate (=8,87-0.03H-0.20A), ATPase (=0.05+0.00H-0.02A), adenosine triphosphate (ATP) (=13.19-0.19H+0.86A).